Notational analysis of the game actions performed by female volleyball players in university competition - Medina-Carrillo, J.; García-Tormo, J. V.; Morante-Rábago, J. C.; Rodríguez-Marroyo, J. A. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2016)
In recent years there have been a lot of studies that have implemented the notational analysis to the study of the technical-tactical behaviours of the athletes in competition. The aim of this study is to describe the type of actions carried out in relationship with the role of the playerby players of volleyball during the competition. Apply principles of notational analysis to a total of 19635 actions, corresponding to 3 sets of each of the 8 teams that participated in the Female Volleyball University Spanish Championship. Among the actions taken by the specific roles of the player, the middleblocker carried out more blocks (25,4%), the setter of setting (31,6%), and the receiver, libero and opposite of dig (38,5; 40,6 and 42,9%, respectively).The knowledge of the actions performed by the players is a great help in the optimization of the performance, because it allows the design of specific tasks depending on the role of the players.